The personal characteristics that influence tax auditors' conciliatory style: An empirical study - Nordin Z.S.; Muhammad, I; Wahab K.A.; Nor Asiah Yaakub (Universiti Putra Malaysia, 2024)
Indexed by SCOPUS/ERA